Does Job Polarization Explain the Rise in Earnings Inequality? Evidence from Europe - Bussolo, Maurizio; Torre, Ivan; Winkler, Hernan (World Bank, Washington, DC, 2018)
Earnings inequality and job polarization have increased significantly in several countries since the early 1990s. Using data from European countries covering a 20-year period, this paper provides new evidence that the decline of middle-skilled occupations and the simultaneous increase of high- and low-skilled occupations are important factors accounting for the rise of inequality, especially at the bottom of the distribution. Job polarization accounts for a large share of the increasing inequality between the 10th and the 50th percentiles, but it explains little or none of the increasing inequality between the 50th and 90th percentiles. Other important developments during this period, such as changing wage returns, higher educational attainment, and increased female labor force participation, account for a small portion of the changes in inequality.